User's attitude and perceptions on the navigability of academic library websites from selected members of South Manila Educational Consortium (SMEC) libraries - Bundalian, Jorge B. (2015)
The study determined the user's attitudes and perceptions on the navigability of the library websites of selected South Manila Educational Consortium (SMEC) libraries. It aimed to a) measure the user's perception of the library website based on satisfaction and perceived value; b) gauge the user's attitude towards the website based on navigability; and c) find out if gender, age, educational attainment, length of inherent experience, and hours spent on the web per day affect the user's attitudes and perceptions of their library websites. A total of 126 library website users participated in the study. The selected SMEC libraries are Adamson University, De La Salle University, Philippine Normal University, St. Scholastica's College, and University of the Phillipines-Manila.